Hart y la configuración del Estado jurisdiccional (2008)
The article suggests the plausibility in the Colombian context of the contemporary assumption that the receipt of the tenets of judicial discretion raised by Herbert Hart, form the basis of the configuration of what Carl Schmitt called the state court. The research draws on both the conceptual definition of the State’s role as the judicial discretion exercised by the judge in accordance to Hart’s view, which has had a strong influence in Latin America, especially in regard to the role played by constitutional judges, to conclude that in the context of current constitutional courts, judicial discretion has not only led to an internal conflict in the classical tripartite division of public power, but also to the configuration of a State where large social, political and economic issues are resolved by individuals who exercise a political role but lacking a responsibility of the same tenor